2018
DOI: 10.1055/s-0038-1642023
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nerve Compression Accelerates the Progression of Diabetic Peripheral Neuropathy in a Rat Model: A Study of Gene Expression Profiling

Abstract: Our study suggests that additional silicone tube wrapping on the SCN of rat with diabetes closely mimics the course and pathologic findings of human DPN. Further studies are needed to verify the effectiveness of this rat model of DPN and elucidate the roles of the individual genes in the progression of DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The double crush hypothesis states that a diabetic nerve is more susceptible to compression than a nondiabetic nerve (7). Another study has reported that chronic nerve compression could accelerate the progression of diabetic neuropathy in the rat model (22). Therefore, diabetic nerve entrapment is a complicated process in which 2 factors of diabetic neuropathy and nerve entrapment interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The double crush hypothesis states that a diabetic nerve is more susceptible to compression than a nondiabetic nerve (7). Another study has reported that chronic nerve compression could accelerate the progression of diabetic neuropathy in the rat model (22). Therefore, diabetic nerve entrapment is a complicated process in which 2 factors of diabetic neuropathy and nerve entrapment interact with each other.…”
Section: Discussionmentioning
confidence: 99%
“…While processes related to lipid and glucose metabolism, response to insulin, and apoptosis regulation were inhibited after diabetes induction, chronic nerve compression further enhanced these inhibitions." 42 Thus the application of ND to treat DSPN has some scientific basis and support.…”
Section: Other Nerve Decompression Studiesmentioning
confidence: 99%